Cutaneous hyperpigmentation of the distal digits. A transient neonatal dermatosis. - Rovatti, G.; Cutrone, M. (European Journal of Pediatric Dermatology, 2000)
This paper is concerned with five cases of isolated melanotic hyperpigmentation of the distal digits (IMHDD) observed in otherwise healthy infants aged less than six months without any significant skin abnormalities. Such condition is transient and subsides by the age of twelve months. Even though it is not an unknown clinical entity, literature on the subject is scarce. We propose that the IMHDD should be classified among transient neonatal dermatoses.